Organocatalyzed [3+3] Annulations for the Construction of Heterocycles - Zhu, Yannan; Huang, You (Synthesis, 2020)
Six-membered heterocyclic systems are widely distributed in many natural products and pharmaceuticals, and the construction of highly functionalized six-membered heterocyclic compounds is an important topic in modern organic synthesis. Organocatalyzed [3+3] annulations represents an important method for assembling a substantial variety of six-membered cycles that contain one or more heteroatoms. This review describes the development of organocatalyzed [3+3] annulations for the synthesis of six-membered heterocycles, including organocatalysis using secondary amines, tertiary amines, phosphines, chiral phosphoric acids and N-heterocyclic carbenes.1 Introduction2 Secondary Amine Catalyzed [3+3] Annulations2.1 Synthesis of Nitrogen Heterocycles2.2 Synthesis of Oxygen Heterocycles2.3 Synthesis of Sulfur Heterocycles3 Tertiary Amine Catalyzed [3+3] Annulations3.1 Catalysis through Multiple Hydrogen-Bonding Interactions3.2 Catalysis of Tertiary Amines as Lewis Bases4 Phosphine-Catalyzed [3+3] Annulations4.1 Synthesis of Nitrogen Heterocycles4.2 Synthesis of Oxygen Heterocycles4.3 Synthesis of Heterocycles Containing Two or More Heteroatoms5 Chiral Phosphoric Acid Catalyzed [3+3] Annulations5.1 Synthesis of Nitrogen Heterocycles5.2 Synthesis of Heterocycles Containing Two or More Heteroatoms6 N-Heterocyclic Carbene Catalyzed [3+3] Annulations6.1 Synthesis of Nitrogen Heterocycles6.2 Synthesis of Oxygen Heterocycles6.3 Synthesis of Heterocycles Containing Two or More Heteroatoms7 Conclusion and Outlook
Keywords: annulations; heterocycles; organocatalysis; amines; phosphines; chiral phosphoric acids; N-heterocyclic carbenes